PEMERIKSAAN DAN PENYULUHAN KESEHATAN DI DESA WANAMEKAR KABUPATEN GARUT - Gin Gin Sugih Permana; Eva Daniati; Andhika; Dede Suharta; Eti Suliyawati; K Dewi Budiarti; Mohamad Riidwan Rifai (Jurnal Pengabdian Masyarakat DEDIKASI, 2020)
Indonesia is a disaster laboratory with 13 types of disasters in it. The history of disaster events shows that there has been an increase in disasters over time. Increasing vulnerability factors and limited capacity also lead to increased disaster risk in the future. This is a challenge in disaster management. Disaster management is local in nature. The purpose of community service activities is that it is hoped that the mindset of the community towards health in Wanamekar village will change, think positively about their health and be more enthusiastic about life and with the PTM examination it can help find out what prevention must be done, and free medical treatment to help people who are sick. The technique for implementing this activity is to do motivation, check uric acid, blood sugar, cholesterol and blood pressure for the community. As for the conclusion: a small proportion of Wanamekar villagers who have difficulty in getting clean water experience psychosocial problems, then many physical problems also occur in the elderly and adults. Hopefully this community service activity will provide benefits for Wanamekar residents.